A correlation between fractal growth, water contact angle, and SERS intensity of R6G on ion beam nanostructured ultra-thin gold (Au) films - Jasrotia, Priya; Priya, Bhanu; Kumar, Raj; Bishnoi, Priyanka; vij, Ankush; Kumar, Tanuj (Frontiers in Physics, 2023)
This work reports the SERS (Surface Enhanced Raman Scattering) detection of rhodamine-6G on gold nanostructures (AuNS) of different sizes under ion beam irradiation. Thermal evaporation was used for the deposition of Au thin film on a glass substrate. Subsequent irradiation has been performed to tune the size of AuNS using 10 keV Ar+ for the fluences ranging from 3×1014 to 3×1016 ions/cm2. The growth of AuNS is found to be governed by ion beam-induced sputtering and diffusion mechanisms. Rutherford Backscattering spectroscopy (RBS) confirms the tuning in size and structures of AuNS due to the decrease in Au concentration under ion beam sputtering. Two competitive statistical parameters of fractal dimension (Df) and interface width (w) control the wettable characteristics of AuNS surfaces. A correlation between fractal growth parameters, water contact angle and SERS detection of rhodamine-6G (R6G) has been established. A higher surface coverage area of Au NPs with lower fractal dimensions and water contact angle favors the enhanced SERS detection of R6G. The present study offers new insight in the underlined mechanism(s) of SERS chemical detection for a wider range of roughened metallic surfaces.